Barbarous Crimes in the 21st Century in Nigeria: The Position of Nigerian Legal Constitution on the Menace - Channak, Zaki Mahmed Omar; Amuda, Yusuff Jelili (Journal of Ecohumanism, 2024)
The rate by which crimes and atrocities are committed by the Nigerians especially since the inception of the 21st century is soundly alarming and gradually affecting the peaceful coexistence in Nigeria. It is pathetic that the menace is almost put the youths into misbehavior in the attempt at pursing their livelihood or become rich in life. Based on this background, this paper attempts at dilating the issue of criminals being committed which having to do barbarous crimes that are rampant among Nigerians. Crimes such as homicide, banditry/kidnappings, human trafficking, human rituals/sacrifices, armed robbery, cybercrimes/yahoo, are discussed in this paper. Equally, we dilate on the position Nigerian legal constitution on these crimes. In the course of findings, there is discovery that the menace or crime is increasing in Nigeria society, and the major problem that constitute to it in Nigeria has to do poverty, unemployment, drug abuse, avarice, as well as improper implementation of law etc.. The method applied in this research is quantitative research design. This method deals with discussing the issue in convergent reasoning in a spontaneous way and free flowing manner rather than divergent reasoning. The research makes use of law books, journals, and some other materials on crimes. The paper concludes that a lot of factors are contributed to the felony in Nigeria, such as poverty, unemployment etc. Nevertheless, if proper implementation of law of criminal matters are taken care in Nigerian legal system, the problem of crimes would drastically reduce or totally ameliorated and the nation would achieve emancipation and liberation from the current tragedies.